In Situ Test Study of Characteristics of Coal Mining Dynamic Load - Jiang He; Lin-Ming Dou; Wu Cai; Zhen-Lei Li; Yan-Lu Ding (Shock and Vibration)
Combination of coal mining dynamic load and high static stress can easily induce such dynamic disasters as rock burst, coal and gas outburst, roof fall, and water inrush. In order to obtain the characteristic parameters of mining dynamic load and dynamic mechanism of coal and rock, the stress wave theory is applied to derive the relation of mining dynamic load strain rate and stress wave parameters. The in situ test was applied to study the stress wave propagation law of coal mine dynamic load by using the SOS microseismic monitoring system. An evaluation method for mining dynamic load strain rate was proposed, and the statistical evaluation was carried out for the range of strain rate. The research results show that the loading strain rate of mining dynamic load is in direct proportion to the seismic frequency of coal-rock mass and particle peak vibration velocity and is in inverse proportion to wave velocity. The high-frequency component damps faster than the low-frequency component in the shockwave propagating process; and the peak particle vibration velocity has a power functional relationship with the transmitting distance. The loading strain rate of mining dynamic load is generally less than class 10−1/s.